The level of Moral Judgment in a Sample of Students at the First Basic Education in Tartous Cit: The level of Moral Judgment in a Sample of Students at the First Basic Education in Tartous City (Journal of Hama University, 2025)
The study aimed to identify the level of moral judgment and to identify the difference in moral judgment according tow variables (gender and age) in a sample of students at the first basic education in Tartous city, the sample composed of (125) students, (83) males and (42) females. Researche used moral judgment scale by (Abd-AlFattah, 2002) The results of the study: the major of students exist in the second level of autonomy morality with(80.8%), as for the variable of age, there was a significant difference in moral judgment and for the older ones, while this difference did not appear between males and females
Keywords: Moral Judgment, Students at the First Basic Education